INCREASING SHOPEE CUSTOMER LOYALTY: A STUDY OF SERVICE QUALITY, PRICE, AND CUSTOMER SATISFACTION IN SEMARANG REGENCY - Alfan, Muhammad Khoirul; Rakhman, M. Arif; Nurmiyati, Nurmiyati (Universitas Muhammadiyah Tangerang, 2025)
The topic of this research is to increase Shopee customer loyalty through service quality, price, and customer satisfaction in Semarang Regency. This research is motivated by a decrease in the number of orders and gross sales value at Shopee in the second quarter of 2024. This study discusses a gap in previous research that does not adequately explain the influence of service quality, price, and customer satisfaction on Shopee customer loyalty in Semarang Regency. The research method used quantitative with Structural Equation Modeling (SEM) analysis techniques and a sample of 140 respondents was selected using purposive sampling techniques. The results of the study show that price has a significant and positive influence on Shopee customer loyalty, while service quality and customer satisfaction do not have a significant effect. The conclusion of this study is that Shopee needs to maintain a competitive pricing strategy to increase customer loyalty in Semarang Regency.